Physical parameter optimization of cellulase by Aspergillus niger on solid-state fermentation of sawdust - Solihah Abdullah (School of Bioprocess Engineering, University Malaysia Perlis, 2011)
Enzymatic hydrolysis of cellulose from lignocellulosic waste which is sawdust finds potential application in commercial production of cellulase enzyme. By using Design Expert 7.1.5, the effect of three physical parameters which are moisture content, fermentation time and inoculums size was studied in solid state fermentation for optimum conversion of cellulose to cellulase enzyme using Aspergillus niger ATCC 16404. In order to get highest cellulase production, parameters must be optimized. Screening process was done by using two-level factorial design to investigate the best parameters in the best range that have potential to produce optimal cellulase enzyme. These ranges were taken as the data to be used in the optimization process by using response surface methodology (RSM). Optimal cellulase production obtained was 0.2527 IU/ ml under optimized parameters in the fermentation condition which are moisture content = 140 %, fermentation time = 8 days and inoculums size = 4 ml with the spore concentration of 107 spore/ ml.